The Effect of the 2008 Recession on Gifted Education Funding Across the State of Texas. (July 2018) - Hodges, Jaret; Tay, Juliana; Desmet, Ophélie; Ozturk, Emine; Pereira, Nielsen
The effect of the 2008 Recession has reverberated throughout public education in the United States. This paper examines how the gifted education funding in the state of Texas changed following the Great Recession. The framework of a generalized longitudinal mixed effect model was used to explore this topic. Data acquired from the Texas Education Association included financial and demographic information on Texas School districts (n = 1, 025) between the 1999–2000 and 2014–2015 academic school years. The primary finding was that the Great Recession adversely affected suburban school districts. These districts saw a greater percentage point reduction of budget allocated toward gifted programming (–.24) than rural (–.08), town (–.05), or urban (–.08) school districts (t = 2.72, p < .01).